2013
DOI: 10.1111/jbi.12180
|View full text |Cite
|
Sign up to set email alerts
|

Palaearctic biogeography revisited: evidence for the existence of a North African refugium for Western Palaearctic biota

Abstract: Aim In contrast to the attention given to southern Europe both as a centre of speciation and differentiation and as a Pleistocene refugium of Western Palaearctic taxa, North Africa has been relatively neglected. In this paper, we set out to address this shortfall.Location North-West Africa and the Mediterranean.Methods We reviewed the existing literature on the biogeography of North Africa, and carried out analyses of species distribution data using parsimony, nestedness and co-occurrence methods.Results In ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
129
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 129 publications
(192 reference statements)
12
129
0
2
Order By: Relevance
“…Despite being a Pleistocene refugium for several taxa and having a high degree of endemism (Husemann et al 2014), the eastern Mediterranean counts thus far only one known species of Charinus, the parthenogenetic C. ioanniticus. This species is recorded from Greece (Kritscher 1959), Turkey (Kovařík & Vlasta 1996;Weygoldt 2005;Seyyar & Demir 2007), Egypt (El-Hennawy 2002) and Israel (Kraus 1961;Rosin & Shulov 1960).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a Pleistocene refugium for several taxa and having a high degree of endemism (Husemann et al 2014), the eastern Mediterranean counts thus far only one known species of Charinus, the parthenogenetic C. ioanniticus. This species is recorded from Greece (Kritscher 1959), Turkey (Kovařík & Vlasta 1996;Weygoldt 2005;Seyyar & Demir 2007), Egypt (El-Hennawy 2002) and Israel (Kraus 1961;Rosin & Shulov 1960).…”
Section: Introductionmentioning
confidence: 99%
“…Studies done with different animal groups found that for most of them this barrier has been of major biogeographic importance (Husemann et al 2014). Our comparison between bird assemblages of the same habitat on opposite sides of the Mediterranean contributes to the understanding of its potential role structuring forest bird communities.…”
Section: Guild Assemblagementioning
confidence: 94%
“…While it seems clear that the Mediterranean is more permeable to birds than to most other groups of animals so far studied (Husemann et al 2014), this barrier could also have an indirect impact on bird assemblages by acting on the distribution of species that are important for birds, as either resources or predators. For example, tree diversity is lower on the southern side of the Strait, and part of that difference has been attributed to historical biogeographic processes (Rodríguez-Sánchez et al 2008).…”
Section: Species Compositionmentioning
confidence: 99%
See 2 more Smart Citations